2010
DOI: 10.1007/s10439-010-0207-z
|View full text |Cite
|
Sign up to set email alerts
|

Shape Variability of Potentials Recorded by a Single-Fiber Electrode and its Effect on Jitter Estimation

Abstract: Technical problems accompanying the recording of fiber pair potentials introduce certain instability in the peak-to-peak interval (rise-time, RT) of these potentials. This study aims (1) to measure the variability observed in RT of a large number of sets of consecutive potentials recorded by a single-fiber (SF) electrode and (2) to evaluate the effect of such variability on the jitter estimation. Using a SF electrode, 140 sets of consecutive potentials were recorded from the m. tibialis anterior of four health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…We also found that higher antibody titers were associated with higher generalization rates, also in agreement with previous studies . The relatively low incidence of positive RNS findings in our series is in agreement with previous work, and is consistent with the low rate of generalization in this subgroup. Presence of thymoma has been previously associated with more severe forms of myasthenia, especially in the setting of positive ryanodine receptor antibodies .…”
Section: Discussionsupporting
confidence: 93%
“…We also found that higher antibody titers were associated with higher generalization rates, also in agreement with previous studies . The relatively low incidence of positive RNS findings in our series is in agreement with previous work, and is consistent with the low rate of generalization in this subgroup. Presence of thymoma has been previously associated with more severe forms of myasthenia, especially in the setting of positive ryanodine receptor antibodies .…”
Section: Discussionsupporting
confidence: 93%
“…There are some limitations in this retrospective study. Restricted clinical condition and examination methods, unwillingness of partial patients and missing data from medical records resulted in small sample size of clinical variables, especially RNS tests in our cohort, but the percentage of patients who entered the final statistical analysis and of those with positive RNS tests were comparable to other studies [7,24,29]. This supported that the conclusions from statistical analysis in this study were reliable.…”
Section: Predictors Of Conversion To Gmgsupporting
confidence: 83%
“…Variability of the shape of potentials measured using SFE was also studied by Rodriquez et al who found that the rise time variability was a sensitive indicator of whether the shape of the second peak was stable or not. Our results corroborate their findings that in some cases, the presence of components from distant fibres may lead to either notch in the negative peak or an inflection in the rising part.…”
mentioning
confidence: 89%